KARAKTERISASI MASSA CETAK DAN TABLET VITAMIN C DENGAN KOMBINASI PATI PREGELATINASI UMBI TALAS PRATAMA DAN AVICEL PH 102 SEBAGAI FILLER-BINDER - Fitriyani, Gita; Nawangsari, Desy; Fauziah (Kartika : Jurnal Ilmiah Farmasi, 2024)
Making vitamin C tablets using felt directly because this material is very sensitive to heat.. However, direct felting is difficult to do due to the poor flow of vitamin C, so it is necessary to add excipients such as starch and Avicel PH 102. This study aims to evaluate vitamin C tablets with a combination of pregelatinized starch of primary taro tubers and Avicel PH 102 as a filler-binder. The study was conducted in a laboratory experiment with five different formulas: F1 (1:0), F2 (0:1), F3 (1:1), F4 (1:3), and F5 (3:1). Flow rate results F2, F3, F4, and F5 are eligible, while F1 is not. All formulas meet the requirements of break angle, uniformity of weight, size, and crushing time. F2 meets the requirements of compressibility and hausner ratio, as well as hardness and brittleness. The results of the F1, F2, F4, and F5 solutions are eligible, while F3 is not. The conclusion of this study is that Avicel PH 102 is better at increasing the flow rate, compressibility, and hausner ratio than the pregelatinized starch of primary taro tubers. The five, requirements are met by this formula, including uniformity in weight, size and disintegration time. The use of Avicel PH 102 results in high hardness and low brittleness, while pregelatinized starch results in low hardness and high brittleness. F1, F2, F4, and F5 qualify for resolution, while F3 does not